1987
DOI: 10.1111/j.1365-2265.1987.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Growth Hormone Response to Growth Hormone‐releasing Hormone in Children With Simple Obesity: Evidence for Somatomedin‐c Mediated Inhibition

Abstract: We have evaluated the plasma GH response to a single injection of 1 microgram/kg of GH-releasing hormone (GHRH)-40 in 15 obese children and 15 age-matched control children. Most of the obese children showed a subnormal plasma GH response to GHRH and the mean plasma GH integrated area (IC-GH) following stimulation was significantly smaller in obese than control children. Plasma somatomedin-C (SM-C) levels were significantly higher in obese than control children, and were negatively correlated with the peak plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 32 publications
5
57
1
2
Order By: Relevance
“…It is suggested that the growth of obese children is not GH dependent but nutrition dependent, since GH secretion by GRF is significantly smaller in SO than in NS as shown in this study and other studies [2,17]. However, IGF-I level is significantly greater in obese children than in normal short children despite lower GH secretion.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…It is suggested that the growth of obese children is not GH dependent but nutrition dependent, since GH secretion by GRF is significantly smaller in SO than in NS as shown in this study and other studies [2,17]. However, IGF-I level is significantly greater in obese children than in normal short children despite lower GH secretion.…”
Section: Discussioncontrasting
confidence: 36%
“…IT HAS been reported that children with simple obesity (SO) show increased linear growth with normal or high serum insulin-like growth f actor-I (IGF-I) levels during prepubertal period, despite low GH secretion [1,2]. On the other hand, insulin secretion is increased in these children [3].…”
mentioning
confidence: 99%
“…49,50 High plasma insulin like growth factor-1 (IGF1) concentrations and reduced growth hormone (GH) secretion (spontaneous or in response to a wide variety of stimuli) are characteristic features of children with simple obesity. 51 Increased IGF1 could promote hyperplasia in all tissues, including adipose tissue, and decreased GH levels could decrease lipolysis, promoting the development and maintenance of large fat stores. A study conducted in 2.5-year-old Danish children found that animal protein (from milk but not from meat or vegetables) was positively associated with serum IGF-1 concentrations and height.…”
Section: Factors Associated With An Early Ar and Increased Fatnessmentioning
confidence: 99%
“…However, findings of studies on obese subjects are conflicting, with serum concentrations of total IGF-I reported to be relatively low, 13-16 unchanged 17,18 or increased. 19,20 Several crosssectional studies of adiposity and circulating IGF-I have found no relationship [21][22][23][24][25][26][27][28][29][30][31][32] while a nonlinear relationship of body mass index (BMI) with IGF-I has been observed in some large studies. [33][34][35][36] The data on the relationship between IGFBP-3, the main binding protein of IGF-1, and obesity are not consistent.…”
Section: Introductionmentioning
confidence: 99%